PENGARUH KONSENTRASI KALSIUM KLORIDA TERHADAP MUTU ANDALIMAN - Roida Ervina Sinaga (Universitas Quality, 2018)
Andaliman is one type of exotic plant in Indonesia, because it has a distinctive aroma and taste and is known to only grow in certain areas in the North Sumatra region. Andaliman is thought to have good prospects, so at this time the farmers have started to cultivate it. Fresh food without processing and preservation will eventually experience changes due to mechanical, physical, chemical and biological effects including physiology, microbiology and parasites. This study aims to determine the concentration of calcium chloride (CaCl2) with long immersion in 40 minutes. Calcium chloride concentration consists of 4 (four) treatments, namely: K1 = 0%, K2 = 0.15%, K3 = 0.30% and K4 = 0.45%.